Faustino Aguilar kapangyarihan, kamalayan, kasaysayan : isang metakomentaryo sa mga nobela ni Faustino Aguilar - San Juan, E. (Epifanio) Jr. 1938- (University of Santo Tomas Publishing House, 2020)
Literary criticism of the works of Faustino Aguilar, a Filipino novelist.